Analisis Penerapan Etika Bisnis Islam dalam Meningkatkan Kepuasan Nasabah di Koperasi Sunan Drajat Lamongan - Abdullah Zawawi (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2023)
This study aims to determine the effect of the application of Islamic business ethics on member satisfaction in the Sunan Drajat Lamongan Cooperative, East Java, Indonesia. This study uses a qualitative method. The location of this research was carried out at the Sunan Drajat Lamongan Cooperative which is located in Banjaranyar Village, Banjarwati, Paciran District, Lamongan Regency. The instruments used in this qualitative method are guidelines or special methods so that in collecting data, it is easy to process the data, and so that the work is easier and the results are better in collecting data. The author uses two sources of data, namely: Primary data and secondary data The results of this study indicate that, first, based on the exposure of the research data, it can be seen that Islamic business ethics carried out by the Sunan Drajat Lamongan Cooperative, in general, are in accordance with Islamic business ethics taught in Islam which include not committing usury, justice to all members and also What responsibilities have been entrusted by its members? Second, from the application of Islamic business ethics in increasing customer satisfaction implemented by the Sunan Drajat Lamongan Cooperative so far it has been going well, as evidenced by the existence of several efforts made by the Sunan Drajat Sharia Cooperative in increasing the number of customers each year.